Examining Think Talk Write (TTW) Strategy in Students’ Vocabulary Mastery - Qomariyah, Siti Syafiatul; Nafisah, Bq Zuhrotun (JOLLT Journal of Languages and Language Teaching, 2020)
This research aimed at finding out the effect of Think-Talk-Write (TTW) in students’ vocabulary mastery. This research was conducted in the first-grade students of Junior High School 5 Praya in the academic year 2019/2020. This research used an experimental design in which it employed two groups pre-test and post-test. The experimental group was treated by using TTW, while the control group was treated by using Acrostic strategy. The two classes were chosen as the samples in this research which consist of 46 students. In analyzing the data, researchers applied statistical analysis. The result of the research showed that there was a significant effect of Think-Talk-Write (TTW) in students’ vocabulary mastery. The finding shows that the t-test value was higher than the t-table (8.693>1.680). Therefore, it comes to the conclusion that the hypothesis set is accepted (Ha).